2017
DOI: 10.1021/acs.jpclett.7b02820
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation Facilitates Proton Transfer through Two-Dimensional Honeycomb Crystals

Abstract: Recent experiments have triggered a debate about the ability of protons to transfer through individual layers of graphene and hexagonal boron nitride (h-BN). However, calculations have shown that the barriers to proton penetration can, at more than 3 eV, be excessively high. Here, on the basis of first principles calculations, we show that the barrier for proton penetration is significantly reduced, to less than 1 eV, upon hydrogenation even in the absence of pinholes in the lattice. Analysis reveals that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
105
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(113 citation statements)
references
References 53 publications
7
105
1
Order By: Relevance
“…These discoveries were absolutely unexpected since graphene was believed to be completely impermeable to all atoms and molecules under ambient conditions [3,4]. A number of works have subsequently appeared -both experimental [5][6][7][8][9][10] and theoretical [11][12][13][14][15][16]-not only stimulated by the promise of important applications in hydrogen technology but also with the aim to uncover the microscopic mechanisms underlying these observations.…”
Section: Introductionmentioning
confidence: 99%
“…These discoveries were absolutely unexpected since graphene was believed to be completely impermeable to all atoms and molecules under ambient conditions [3,4]. A number of works have subsequently appeared -both experimental [5][6][7][8][9][10] and theoretical [11][12][13][14][15][16]-not only stimulated by the promise of important applications in hydrogen technology but also with the aim to uncover the microscopic mechanisms underlying these observations.…”
Section: Introductionmentioning
confidence: 99%
“…Further measurements involving hydrogen's isotope deuterium have shown that this barrier is in fact 0.2 eV higher than the measured activation energy because the initial state of incoming protons is lifted by zero-point oscillations at oxygen bonds within the proton-conducting media used in the experiments 2 . The resulting value of 1.0 eV for the graphene barrier is somewhat lower (by at least 30%) than the values obtained theoretically for ideal graphene 1,[8][9][10][11] , which triggered a debate about the exact microscopic mechanism behind the proton permeation [8][9][10][11][12][13] . For example, it was recently suggested that graphene's hydrogenation could be an additional ingredient involved in the process 11 .…”
mentioning
confidence: 71%
“…The resulting value of 1.0 eV for the graphene barrier is somewhat lower (by at least 30%) than the values obtained theoretically for ideal graphene 1,[8][9][10][11] , which triggered a debate about the exact microscopic mechanism behind the proton permeation [8][9][10][11][12][13] . For example, it was recently suggested that graphene's hydrogenation could be an additional ingredient involved in the process 11 . Furthermore, it was shown experimentally that graphene's barrier for protons could be lowered quite substantially by decorating graphene with nanoparticles of catalytically-active metals such as Pt and Pd 1 .…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Partly because of the fascinating measurements, considerable theoretical effort have gone into understanding the microscopic details of how protons penetrate graphene and h-BN and to understand the role of NQEs in the process [159,[163][164][165]. In work that we were involved in, we used DFT-based PIMD to examine the proton penetration process [165]. With the specific DFT functional used and model system employed we found that the classical H + penetration barrier was approximately 3.5 eV, in line with earlier studies.…”
Section: Proton Penetration Of 2d Materialsmentioning
confidence: 99%